Uji Alat Pengering Pisang Tipe Rak Energi Surya Dan Biomassa - Mario Rinaldo Masela; Jamaludin Jamaludin; Ni Luh Sri Suryaningsih; Toni Mulyono (Musamus AE Featuring Journal, 2019)
Banana chips drying is an important process in flouring. Conventional drying has many drawbacks such as long drying time, large areas, quality degradation due to dirt, and unpredictable rain can occur. The purpose of this study was to test the banana dryer for solar and biomass rack energy types. The stages of this research are the design of a rack type banana dryer, the manufacture of parts for tools, and the testing of dryers. The test was carried out with three treatments, namely drying with a solar energy dryer, biomass energy dryer, and conventional drying as a control. Drying test was carried out for 600 minutes with an initial sample water content of 69.33%. During the test, banana samples were taken to measure temperature and water levels every 30 minutes. The test results showed the moisture content of banana chips on drying using the lowest biomass energy compared to conventional solar energy dryers and drying. The final moisture content of banana chips on the rack 5 solar energy dryers and biomass energy dryers is 22% and 16%, respectively. Whereas, in conventional drying, the final moisture content of banana chips is 33.33%.